THE EFFECTIVENESS OF TELEMEDICINE FOR BREAST CANCER DISEASE MANAGEMENT: A SYSTEMATIC REVIEW AND META-ANALYSIS - Wangwatcharakul, Warattaya; Kapol, Nattiya; Bunchuailua, Waranee (Thai Bulletin of Pharmaceutical Sciences, 2018)
Breast cancer is an important public health problem affecting both physical and mental status of Thai women patients. Currently, telemedicine has been used in counseling and providing mental health support for breast cancer patients. There have been a number of studies revealing the effectiveness of telemedicine in various aspects. This study aimed to systematically review and conduct a meta-analysis on the effectiveness of telemedicine for breast cancer disease management. Published reports were searched through the electronic databases including PubMed, Scopus, Cochrane Library, and Thai databases from inception to January 2016. Randomized controlled trials reporting clinical or humanistic outcomes were selected. Results showed that 22 articles were identified consistent with inclusion criteria. Telemedicine was used to monitor symptoms, educate and advise the patients on self-care, and cope with problems through telephone, e-mail, website, and letter. Measured outcomes were mortality rates, adherence, recurrence, coping with problems, psychological and psychosocial status, and quality of life. The meta-analysis indicated no significant differences in the quality of life of the patients receiving telemedicine and those receiving the usual care practice, regarding the overall quality of life (standardized mean difference (SMD) = 0.10; 95%CI: -0.14, 0.35; p-value = 0.41); role of functioning domain (MD = -2.12; 95% CI: -6.95, 2.70; p-value = 0.39); emotional functioning domain (MD = -1.62; 95% CI: -5.75, 2.51; p-value = 0.44), and fatigue domain (MD = 5.28; 95% CI: -2.45, 13.01; p-value = 0.18). However, further studies should be conducted on the use of telemedicine for breast cancer management as a supplement or a replacement of usual care.